Pengaruh Karbopol dan Propilen Glikol terhadap Laju Penetrasi Sediaan Emulgel Xanthone Rich Fraction dari Kulit Buah Manggis (Garcinia mangostana L.) - Dahlizar, Sabrina; Alifia Agustina, Putri; Fitriana, Narti; Wira Septama, Abdi; Fajriah, Sofa; Herdini, Herdini (ALCHEMY:Journal of Chemistry, 2023)
Xanthone Rich Fraction (XRF) derived from mangosteen rind (G. mangostana L.) contains α-mangostin possessed antioxidant property. It may be used to prevent aging (anti-aging). This study aims to determine the effect of adding Carbopol as a gelling agent and propylene glycol as an enhancer on the physical characteristics and penetration rate of the emulgel. Four different formulas were prepared, F1 without a gelling agent (Carbopol) and enhancer (propylene glycol), F2 without a gelling agent (carbopol), F3 using a gelling agent (carbopol), and F4 using a gelling agent (carbopol) and enhancer (propylene glycol). The physical properties of formulas such as organoleptic examination, pH, viscosity, homogeneity, spreadability and cycling test were evaluated. Penetration testing was carried out using a Franz Diffusion cell. The results showed that F3 and F4 had the best physical stability and there was a difference in the penetration rate of α-mangostin from the four formulas. The amount of α-mangostin expanding the area for 6 hours, F1, F2, F3 and F4 were 228,22 µg/cm2; 251,06 µg/cm2(Tabel 3); 852,24 µg/cm2; dan 1.087,15 µg/cm2 respectively. The addition of a combination of Carbopol (gelling agent) and propylene glycol (enhancer) showed the highest penetration rate